Developing of Organizational Citizenship Behavior in Supervisors at PT. PLN NP, Tbk through Improving the Quality of Work of Life - Moh. Ghufran; Faruk Faruk; Arif Hidayat (Institute of Computer Science (IOCS), 2026)
Companies operating in the sector of meeting people's basic needs and using high technology are required to be able to provide quality services. HR management plays an important role, and efforts to improve the quality of HR require development strategies, one of which is building a culture of organizational citizenship behavior (OCB). One way that is considered effective is by improving quality of work of life (QWL) to build OCB. This descriptive research took 42 employees holding supervisory positions at PT. PLN NP Surabaya, data was collected through HR assessment documents and Thurstone scale model questionnaires. The results of factor analysis show that QWL is represented in three components that influence OCB, namely the benefits component, work environment and career development. Aspects of OCB that can be observed are communication and feedback, which appear in the form of alturism, namely employees showing an attitude of being willing to help colleagues who need help, and civic virtue, such as involving themselves in company activities even though these activities are not needed in their work. This research proves that QWL has a positive and significant effect on the formation of OCB at PT. PLN NP in Surabaya.